On the History and Hermeneutics of Comics Journal for Religion, Film and Media - Christian Wessely (Journal for Religion, Film and Media, 2017)
What is a comic? The simple answer states that a comic is a drawn story that is picture- rather than text-oriented and told serially. In other words, a comic is a type of illustration. Realism is not its goal; rather a narrative is developed through reduction according to specific stylistic means. I start this article with a definition of the term "comic", and move on to highlight the complexity of the comic and to argue that insight into this complexity is necessary for its correct interpretation. Only then can we recognise that the comic is not only entertaining but also, in its own way, a vehicle for content that might be system confirming and propagandistic but can also be system critical. Doing so allows us to see the potential of the comic that is embedded in its particular affinity with nonlinear interactive audiovisual media.